P+2+9p=6(2p-7)-2(p-6)

Simple and best practice solution for P+2+9p=6(2p-7)-2(p-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P+2+9p=6(2p-7)-2(p-6) equation:


Simplifying
P + 2 + 9p = 6(2p + -7) + -2(p + -6)

Reorder the terms:
2 + P + 9p = 6(2p + -7) + -2(p + -6)

Reorder the terms:
2 + P + 9p = 6(-7 + 2p) + -2(p + -6)
2 + P + 9p = (-7 * 6 + 2p * 6) + -2(p + -6)
2 + P + 9p = (-42 + 12p) + -2(p + -6)

Reorder the terms:
2 + P + 9p = -42 + 12p + -2(-6 + p)
2 + P + 9p = -42 + 12p + (-6 * -2 + p * -2)
2 + P + 9p = -42 + 12p + (12 + -2p)

Reorder the terms:
2 + P + 9p = -42 + 12 + 12p + -2p

Combine like terms: -42 + 12 = -30
2 + P + 9p = -30 + 12p + -2p

Combine like terms: 12p + -2p = 10p
2 + P + 9p = -30 + 10p

Solving
2 + P + 9p = -30 + 10p

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + P + -2 + 9p = -30 + -2 + 10p

Reorder the terms:
2 + -2 + P + 9p = -30 + -2 + 10p

Combine like terms: 2 + -2 = 0
0 + P + 9p = -30 + -2 + 10p
P + 9p = -30 + -2 + 10p

Combine like terms: -30 + -2 = -32
P + 9p = -32 + 10p

Add '-9p' to each side of the equation.
P + 9p + -9p = -32 + 10p + -9p

Combine like terms: 9p + -9p = 0
P + 0 = -32 + 10p + -9p
P = -32 + 10p + -9p

Combine like terms: 10p + -9p = 1p
P = -32 + 1p

Simplifying
P = -32 + 1p

See similar equations:

| 9z^3-27z^2-792z= | | 1-(8/x^2)=0 | | y=3(-6)+4 | | 9x^4+9x^2+2= | | 3a-2=4-2a | | if(12x)3=(123)xvalue | | 5y^4-33y^2-14= | | 7z^3-21z^2-2646z= | | Xsquared-2=38 | | -7+5M=-3M+5(M+1) | | -14x^2-52x+16= | | 4v^2-22v+10= | | 1+2k-2=-1 | | 3(4x-6)=12+6 | | 12x^2+11=0 | | f(-11)=8x-9 | | (6.25)4/(6.25)3 | | 22.88/10.4 | | x/2.8=5.6 | | 3(k-4)-2(k+2)-13=23 | | 6t+2=t-1 | | ax^2+5a-25-5x^2= | | lnx=-ln(x+1) | | 14x-(8+7x)= | | 4x+(-4-x)=1 | | 0.04(y-9)+0.08y=0.10y-0.5 | | 8(t-4)+4t=4(3t+4)-13 | | x^3+8=(x+2) | | 18-4(2x+2b)=5b-2x | | (2x-3y)dx-(3x+2y)=0 | | 4a^2+b^2+c^2-4ab+2bc-4ca= | | -8x^2-24x-48=0 |

Equations solver categories